2015
DOI: 10.4049/jimmunol.1402276
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Roles of Dectin-1 Expressed on Human Plasmacytoid Dendritic Cells and Myeloid Dendritic Cells in Th2 Polarization

Abstract: Dendritic cells (DCs) can induce and control host immune responses. DC subset-dependent functional specialties and their ability to display functional plasticity, which is mainly driven by signals via pattern-recognition receptors (PRRs), identify DCs as immune orchestrators. A PRR Dectin-1 is expressed on myeloid DCs (mDCs) and is known to play important roles in Th17 induction and activation during fungal and certain bacterial infections. Here, we first demonstrate that human plasmacytoid DCs (pDCs) express … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 45 publications
1
38
2
Order By: Relevance
“…While ligation of ITIM-associated LLR, such as myeloid C-type lectin-like receptor (MICL) or DCIR in cDCs inhibits TLR4 and TLR8 signaling (24, 33, 34), suppression of TLR signaling by ligation of ITAM-associated LLRs in cDCs has not been reported (28). These results together with the recent observation showing that Dectin-1-activated pDCs promote Th2-type T cell responses while Dectin-1-activated cDCs do the opposite, point to the importance of combination of PAMP, PRR, and the cell context in the regulation of adaptive immune responses by innate immunity (4, 35). …”
Section: Immunogenic and Tolerogenic Receptors Of Dcssupporting
confidence: 58%
“…While ligation of ITIM-associated LLR, such as myeloid C-type lectin-like receptor (MICL) or DCIR in cDCs inhibits TLR4 and TLR8 signaling (24, 33, 34), suppression of TLR signaling by ligation of ITAM-associated LLRs in cDCs has not been reported (28). These results together with the recent observation showing that Dectin-1-activated pDCs promote Th2-type T cell responses while Dectin-1-activated cDCs do the opposite, point to the importance of combination of PAMP, PRR, and the cell context in the regulation of adaptive immune responses by innate immunity (4, 35). …”
Section: Immunogenic and Tolerogenic Receptors Of Dcssupporting
confidence: 58%
“…For example, DECTIN-1 signaling in DCs has been shown to influence T-cell polarization fate by modulating also the expression of the costimulatory molecules OX40 ligand. 37 We found that CLEC-1 ligation does not induce by itself nor does it modulate the zymosan-induced activation of the SYK-dependent canonical NF-kB pathway. Nevertheless, we observed changes in the phosphorylation pattern of CLEC-1-binding partners.…”
Section: Cd25mentioning
confidence: 86%
“…2). Transcription of IL12A, encoding the IL-12p35 subunit, depends on chromatin remodelling to allow the 52 . RAF1 activation by dectin 1 also induces epigenetic reprogramming in monocytes, thereby enhancing innate antifungal immunity by monocytes upon a second exposure to the pathogen 53 , and it is conceivable that this process is important in reinforcing adaptive immunity.…”
Section: Dectin 1 Induces T H 1 and T H 17 Cell Responsesmentioning
confidence: 99%